Paleoceanographic perturbations and the marine carbonate system during the middle to late Miocene carbonate crash—a critical review - Preiss-Daimler, I; Zarkogiannis, S; Kontakiotis, G; Henrich, R; Antonarakou, A (MDPI, 2021)
This study intends to review and assess the middle to late Miocene Carbonate Crash (CC) events in the low to mid latitudes of the Pacific, Indian, Caribbean and Atlantic Oceans as part of the global paleoceanographic reorganisations between 12 and 9 Ma with an emphasis on record preservation and their relation to mass accumulation rates (MAR). In the Eastern Pacific the accumulation changes in carbonate and opal probably reflect an El-Niño-like state of low productivity, which marks the beginning of the CC-event (11.5 Ma), followed by decreased preservation and influx of corrosive bottom waters (10.3 to 10.1 Ma). At the same time in the Atlantic, carbonate preservation considerably increases, suggesting basin-to-basin fractionation. The low-latitude Indian Ocean, the Pacific and the Caribbean are all characterised by a similar timing of preservation increase starting at ~9.6–9.4 Ma, while their MARs show drastic changes with different timing of events. The Atlantic preservation pattern shows an increase as early as 11.5 Ma and becomes even better after 10.1 Ma. The shallow Indian Ocean (Mascarene plateau) is characterised by low carbonate accumulation throughout and increasing preservation after 9.4 Ma. At the same time, the preservation in the Atlantic, including the Caribbean, is increasing due to enhanced North Atlantic deep-water formation, leading to the increase in carbonate accumulation at 10 Ma. Moreover, the shoaling of the Central American Isthmus might have helped to enhance Caribbean preservation after 9.4 Ma. Lower nannoplankton productivity in the Atlantic should have additionally contributed to low mass accumulation rates during the late CC-interval. Overall, it can be inferred that these carbonate minima events during the Miocene may be the result of decreased surface ocean productivity and oceanographically driven increased seafloor dissolution.